Once upon a long ago : my life in the bush & the city - Williams, Albert, 1933-; Cracknell, Julie ([Newtown, New South Wales] : CLA Press, 2014)
Stories told by Albert Williams about his working life on various stations and sheering sheds in outback NSW and later at Tranby Aboriginal College in Glebe, where he eventually served on the Board of Directors. Albert Williams was born in 1933 in Brewarrina and grew up in Bourke. His father was a WWII veteran and grandfather a police tracker. Albert's family history describes the importance of Gundabooka Mountain in Ngemba country. The book includes a collection of Albert's poems and paintings, and is dedicated to his grandparents.
Keywords: Williams, Albert, -- 1933-; Tranby Aboriginal College (Glebe, N.S.W.).; Aboriginal Australians -- New South Wales -- Biography; Men -- Australia -- Biography; Defence - World War II; History - Biographies - Indigenous; Law enforcement - Police trackers; Gamilaraay / Gamilaroi / Kamilaroi people (D23) (NSW SH55-12); Ngiyampaa / Ngemba people (D22) (NSW SH55-10); History - Genealogy and family history; Defence - Armed forces; Education - Adult education; Sydenham (Inner west Sydney NSW SI56-05); Tilpa (NW NSW SH55-09); Glebe (Inner Sydney NSW SI56-05); Brewarrina (N NSW SH55-06); Murdi Paaki / Bourke (N NSW SH55-10); Byrock (N NSW SH55-10); Australian